Rare-earth and major elements concentration in manganese nodules from the Northwest Atlantic - Sunit Kumar Addy (PANGAEA, 2022)
The shale-normalized REE patterns of manganese nodules from the northwest Atlantic show enrichment in Sm and Eu relative to the heavier and lighter REE, excluding Ce, and are similar to the patterns previously observed in deep water (> 3000m) nodules from the Pacific. The inverse relation of this pattern to that of sea water and the high Ce anomaly (average 5.5) indicate that probably the REE in the nodules originate from sea water and the nodules are possibly hydrogenous. The patterns for micronodules are similar to those of the nodules but the concentrations of REE were substantially higher in two of them. The red clay occurring on abyssal hills where nodules and micronodules are found also shows higher REE concentrations over terrigenous gray clay. The latter is devoid of nodules and micronodules and occurs in abyssal plains. The excess REE in the red clay also show a pattern similar to those of the nodules and micronodules. Most of the micronodule samples show a lower Ce anomaly (1.7) and lower Co concentration compared to the nodules, so it is inferred that at least some micronodules were formed during post-depositional periods when the conditions were less oxidizing than average.
In: Addy, SK (2022): Rare earth element composition of manganese nodules and micronodules from the northwest Atlantic [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.943839